COMPARATIVE ASSESSMENT OF HATCHING PERFORMANCE OF TURKEY (Meleagris gallopavo) VARIETIES - A. Clement Ebenezer Henry; P. N. Richard Jagatheesan; A. Paramasivam; C. Mehala (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was carried out to assess the hatching performance of five turkey varieties maintained under standard mangemental practices at TANUVAS – Regional Research Centre, Pudukkottai. The hatching eggs from different breeder turkey varieties, viz. Nandanam – I, Nandanam – II, Beltsiville Small White, Broad Breasted Bronze and Desi – Turkey were collected and incubated as per standard procedure. Hatchability and fertility showed significant difference (P < 0.01) between the five turkey varieties studied. The highest total hatchability (66.92 %) and fertile hatchability (77.98 %) was observed in Nandanam – II turkey. Fertility was highest in Beltsville Small White (87.74%). There was no significant (P > 0.05) difference in late embryonic mortality between different varieties, but early embryonic mortality was found to be more in Broad Breasted Bronze and differed significantly (P < 0.01) with other turkey varieties. The present study reveals that the hatching performance of Nandanam – II and fertility of Beltsville Small white was better in Pudukkottai district.